Deceived by desire - Force, Marie (Force, Marie. Gilded series., 2019)
Wealthy American industrialist Aubrey Nelson has invited the Duke and Duchess of Westbrook to visit his family<U+2019>s Newport seaside “cottage” for the summer. With his parents<U+2019> departure from New York delayed, Aubrey<U+2019>s mother sends him ahead to oversee preparations for their guests. But when he arrives, he<U+2019>s surprised to find the house and staff in disarray . . . With much to do and little time, Aubrey comes to rely on the housekeeper, a lovely young Irish woman named Maeve Brown. And when he also finds himself confiding in Maeve about more personal matters, he tells himself it<U+2019>s merely their close proximity that draws him to the compassionate, hard-working beauty. Yet when he suspects Maeve is in danger, Aubrey realizes his feelings for her have grown much deeper than they should have. For what will his mother, who dreams of a society match for her son, have to say when she arrives to discover he<U+2019>s lost his heart to a girl of the working class?